Monitoring and Evaluation of Production Processes An Analysis of the Automotive Industry - Panda, Anton; Jurko, Jozef; Pandová, Iveta; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents topics on monitoring and evaluation of production processes in the automotive industry. Regulation of production processes is also described in details. The text deals with the implementation and evaluation of these processes during the mass production of components useful in the automotive industry. It evaluates the effects and results achieved after implementation in practice. The book takes into account the different methodologies of the world's automakers and applicable standards, such as standard EN ISO 9001 and the requirements of VDA and ISO/TS 16949. The content is used to those working with the development, production and quality control of new products in the demanding automotive industry. The information provided may also be useful to engineers and technical staff in organizations working with series production and production of spare parts for the automotive and other demanding industries. The content presented was written based on discussions with various companies and organizations, such as Magna Steyr (Graz, Austria), Ford (Cologne, Germany; Prague, CZ), GM Powertrain (Győr, Hungary), VW (Škoda), ZF (Passau, Friedrichshafen, Germany), Bosch-Rexroth AG (Fellbach, Germany), John Deere (Mannheim, Germany; USA), Claas (Paderborn, Germany), Allison Transmission (USA), Landini (Reggio Emilia, Milan, Italy), Timken Polska (Sosnowiec, Poland), SNR France (Annecy, France), Sweden SKF Group (Lutsk, Ukraine), ZVL Ltd. (Hattingen, Germany), ZVL SpA (Milano, Italy), FAG Schaeffler Group (Debrecen, Hungary), VPZ (Vologda, Russia), ZKL OJSC (Brno, CZ), ZVL Auto Company Ltd. (Prešov, Slovakia), ZVL (Žilina, Slovakia), MAN (Munich, Germany), FTE Automotive (Kerpen, Germany), Rösler (Untermerzbach, Germany; Vienna, Austria), Spaleck (Bocholt, Germany) and Caterpillar (USA). This comprehensive study was supported by grant VEGA 1/0409/13. .
Introduction -- Setting goals of this work -- Analysis of current state the regulation of manufacturing processes -- Specification of problems solutions -- Deployment of regulation the production processes in the serial production of a specific production company -- Evaluation of capability the production processes -- Evaluation the capability of machine -- Evaluation the capability of gauges -- Capability under the association of automobile manufacturers in Germany (VDA 6.1) -- Automation the control of production processes -- Results and benefits the implementation of regulation and further procedures and methodologies, benefits for science and for practice.
Keywords: Automotive engineering; Manufactures; Security systems; Automobile industry and trade; Automotive Engineering; Machines, Tools, Processes; Security Science and Technology; Automotive Industry